KEBUTUHAN BELAJAR YANG TAK TERLIHAT: EKSPLORASI DUKUNGAN AKADEMIK DAN NON-AKADEMIK BAGI ABK DI SD INKLUSIF - Oktafiastuti; Liftiah Liftiah; Ali Formen (STKIP Subang, 2026)
Inclusive education in elementary schools still faces challenges in meeting the holistic needs of children with special needs, especially the neglected non-academic aspects. This study aimed to explore academic and non-academic support needed by slow learner and physically disabled children in inclusive elementary schools. A descriptive qualitative approach was employed through in-depth interviews, observations, and document analysis. Participants consisted of three classroom teachers, two special assistant teachers, and three parents. The findings reveal that academic support such as initial assessment, curriculum modification, and physical accessibility has not been systematically fulfilled. Non-academic support including emotional regulation for slow learners and social acceptance for physically disabled children remains largely unaddressed. The study concludes that invisible non-academic needs show a wider gap than academic needs. It recommends strengthening social-emotional programs and improving physical accessibility in schools.